Principles of biochemistry - Lehninger, Albert L. (New York : Worth Publishers, Inc., 1982)
This book is intended primarily for students taking their first course in biochemistry. It is a new book, not simply an updating of my earlier books.
Part I. Biomolecules -- Part 2. Bioenergectics and metabolism -- Part 3. Some aspects of human biochemistry -- Part 4. Molecular transmission of genetic information.
Includes index.
Keywords: BIOCHEMISTRY